Testing of a paper-and-pencil Personalized Single Category Implicit Association Test (SC-IAT-P). Issue 1 (12th May 2016) - Bardin, Brigitte; Perrissol, Stéphane; Py, Jacques; Fos, Yoann; Souchon, Nicolas
The purpose of this series of studies is to test a paper-and-pencil procedure adapted from a computerized Implicit Association Test: the SC-IAT-P (Personalized Single Category Implicit Association Test, Bardin, et al. 2014 ). This adaptation combines the advantages of SC-IAT (Karpinski & Steinman, 2006 ), IAT-P (Olson & Fazio, 2004 ) and paper-and-pencil IAT (Lemm, Lane, Sattler, Khan & Nosek, 2008 ). It is capable of measuring implicit attitude toward a single object, limits the influence of extrapersonal associations, and is unquestionably easy to administer. The tool was used in three studies with two different goals. Study 1 highlights a link between paper-and-pencil SC-IAT-P and a computerized corollary in the field of tobacco-smoking. Study 2 reveals the ability of the tool to distinguish smokers from non-smokers according to their score and smokers who have already considered quitting from those who have never considered it. Finally, Study 3, carried out between the two rounds of the French presidential elections in 2012, highlights the difference of attitude between supporters on the Left and Right but also an effect of indecision. The discussion deals with the prospects offered by this tool and its limitations.